Adoption of TANUVAS Aseel backyard chicken adoption by ruralpoultry farmer of Dharmapuri district - THANGADURAI, R; SIVAKUMAR, K; VENNILA, M A (The Indian Journal of Animal Sciences, 2023)
Dharmapuri rural farmers were aware about TANUVAS Aseel strains of backyard poultry and had experience of rearing TANUVAS Aseel chicks trained by KVK, Dharmapuri. About 23.6% of the farmers have discontinued the practice due to lack of awareness about brooding and non-availability of chicks and 22.03% of the farmers did not followed the practice because of low preference and predator attack. Farmers preferred TANUVAS Aseel strain of backyard poultry for meat and egg purpose, who fetch meat cost @ ₹400/kg. Therefore, KVK, VUTRC and Animal Husbandary sector should aid supportive services like brooding, vaccination, feeding, housing, marketing of these birds to the farmers in order to encourage backyard poultry farmers. Conclusively, extension activity should be strengthened for efficient transfer of technology from the laboratory to the farmer field.